PERANAN GURU PAUD DALAM MENINGKATKAN NILAI-NILAI RELIGIUSITAS DAN SOSIALITAS PADA ANAK USIA DINI DI TK AL-INSAN SURABAYA - dari, desi wulan; Arif, Muchamad (Universitas Narotama, 2025)
Concern regarding the decline in religiosity and sociality values in youngchildren, there are young children who do not obey teachers during the teaching andlearning process which is carried out in class and outside of class, fight among friends,do not participate in praying together and say dirty things to teachers and friends. Thisresearch aims to: describe the role of PAUD teachers in instilling religious values andsociality in early childhood at AL Insan Kindergarten Surabaya. The type of researchused in the research is descriptive qualitative research.The research results presentedillustrate that at AL Insan Surabaya Kindergarten, teachers instill and practiceKarimah's moral values in students. They focus on developing a good relationship withAllah, maintaining personal purity, loving each other, helping fellow Muslims, andhaving noble morals towards everyone. The main emphasis is to provide an in-depthunderstanding of moral values in the Islamic religion and encourage students topractice them in everyday life. A safe and supportive environment is created toencourage Karimah's moral practices. Through the application of the values of faith,piety, Karimah morals, and understanding and practicing the teachings of the Islamicreligion, this school aims to form students who are religiously devout and have noblemorals in accordance with Islamic principles.